The Food stylist's handbook : hundreds of media styling tips, tricks, and secrets for chefs, artists, bloggers, and food lovers - Vivaldo, Denise; Flannigan, Cindie (New York, NY : Skyhorse Publishing, 2017)
It takes a steady hand to arrange the chocolate curls and drizzle the caramel sauce in elaborate designs on top of that sumptuous tiered cake. Whether for food blogs, television, books, magazines, movies, menus, or advertising, food stylists and photographers learn to slice, plate, tweak, and arrange so the dish becomes less a bit of food and more the work of an artisan. With Denise and coauthor Cindie Flannigan$1 (Bs help, you$1 (Bll find: how to get started, what equipment you$1 (Bll need, how to find clients, tips to staying successful in the business and how to craft and style food (and products that appear to be food) so it all looks delicious from every angle. The Food Stylist$1 (Bs Handbook has been fully updated and revised to help current culinary professionals, armchair chefs, bloggers, and food photographers understand how to make every picture tell a story.s
Food styling as a career -- What a food stylist does -- The different niches of food styling -- Starting a food styling business -- Building a styling kit -- Marketing your food styling business -- Making money and selling your services -- Preparing for magic time -- Tricks of the trade.
Includes bibliographical references and index.
Keywords: PHOTOGRAPHY OF FOOD